PENGARUH PENGETAHUAN PAJAK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK DENGAN TAX COMPLEXITY SEBAGAI VARIABEL MODERASI - KHUSNUL, ERAWATI; PRASTIWI, DEWI (Jurnal Akuntansi AKUNESA, 2018)
This research examines the effect from tax knowledge on coorporate taxpayer compliance of registered in KPP Pratama Surabaya Sukomanunggal with the addition of tax complexity as a moderating variable. This research uses questionnaire as the basis of data retrieval. Based on test results using linear regression and Moderate Regresion Analysis (MRA) from SPSS 22. The results show that tax knowledge have effect on taxpayer compliance but tax complexity can not moderate the relationship between tax knowledge to taxpayer compliance. This study uses cognitive psychology theory and attribution theory for theoritical basis. Keywords: Tax knowledge, taxpayer compliance, Tax complexity